PENERAPAN METODE PIECES DALAM PENGEMBANGAN SISTEM E-COMMERCE PENJUALAN PRODUK KOMPUTER - Sri Nurhayati; Nur Sucahyo; Selawati Selawati (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
E-commerce is a trading transaction activity through the internet network. By utilizing e-commerce, sellers can offer their products online to make it easier for them to shop, transact, and deliver effectively and efficiently. Using an e-commerce website as a sales tool, will expand the product marketing area and make it easier for buyers to select and order these products to increase the sales turnover of the store. Toko Blora is an electronics store located in Harco Mangga Dua. This shop sells several electronic products ranging from PCs, Laptops / Notebooks, parts, and accessories for PCs and Laptops / Notebooks. The sales system that has been used so far is by offering and marketing products using brochures. This method causes the product sales process to take a long time, in addition to making reports that still use handwriting in recording store sales is considered less effective and efficient. To provide solutions to these problems, it is necessary to create an application system that is expected to be able to manage all existing problems. The purpose of this research is to produce a computer product sales system via the Internet (e-commerce). The research was conducted with a field study method with data collection using observation and interviews. The analysis and design stages used the PIECES method to produce the proposed system. The research result is in the form of a computer product e-commerce system that is applied to the Blora Shop.